2017 Joint IEEE International Conference on Development and Learning and Epigenetic Robotics (ICDL-EpiRob) 2017
DOI: 10.1109/devlrn.2017.8329795
|View full text |Cite
|
Sign up to set email alerts
|

Development of reaching to the body in early infancy: From experiments to robotic models

Abstract: We have been observing how infants between 3 and 21 months react when a vibrotactile stimulation (a buzzer) is applied to different parts of their bodies. Responses included in particular movement of the stimulated body part and successful reaching for and removal of the buzzer. Overall, there is a pronounced developmental progression from general to specific movement patterns, especially in the first year. In this article we review the series of studies we conducted and then focus on possible mechanisms that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Likewise, opening the hand during reaching, although in part driven by central nervous system and maturational changes, may also be influenced by experience. Although we cannot easily vary experiential input to infants, often because of ethical issues, studies that use modeling with artificial agents in which input is systematically varied might help to provide answers to these questions (Hoffmann et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, opening the hand during reaching, although in part driven by central nervous system and maturational changes, may also be influenced by experience. Although we cannot easily vary experiential input to infants, often because of ethical issues, studies that use modeling with artificial agents in which input is systematically varied might help to provide answers to these questions (Hoffmann et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…However, such activation per se does not mean that the infant localizes the stimulus in the sense that she can reach to it. For that, the stimulation needs to be associated with other sensorimotor laws or contingencies (O’Regan, 2011; Hoffmann et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain a more comprehensive picture of how infants respond to tactile stimulation of their body and how they use their gradually developing body knowledge, further studies are needed in which other areas (ears, elbow, trunk, knees, etc.) are stimulated (see Hoffmann et al ., ). Third, the present study does not allow us to explore the possible mechanisms that might generate the observed behaviour and that might underlie infants’ early learning about their body.…”
Section: Discussionmentioning
confidence: 97%
“…Differentiation of body responses has also been investigated by measuring infants’ responses to vibrotactile stimulation (Bremner et al, 2008; Begum Ali et al, 2015; Hoffmann et al, 2017; Somogyi et al, 2018; Chinn et al, 2019). In these experiments, the authors applied a vibrotactile stimulation on the infant’s body for several seconds at different locations (not simultaneously but one location after the other) and measured the ability of the infant to localize the buzzer on a specific body part.…”
Section: Body Knowledge: Is the Agent Able To Identify The Particularmentioning
confidence: 99%